Diffusive thermal treatments combined with PVD coatings for tribological protection of titanium alloys. (5th January 2016) - Marin, E.; Offoiach, R.; Regis, M.; Fusi, S.; Lanzutti, A.; Fedrizzi, L.
Abstract: A wide array of treatments have been applied to improve the tribological behavior of titanium alloys, in particular coatings and diffusive nitrogen treatments. Hybrid technologies based on diffusive treatments and subsequent deposition of PVD coatings may further improve the overall tribological resistance. In this work, conventional PVD coatings of CrN or TiCN, deposited on Ti-6Al-4 V substrates, have been characterized and then combined with two thermal diffusive treatments: nitriding and carburizing. Post-treatment surface morphologies have been studied by means of Scanning Electron Microscopy and Stylus Profilometry. In-depth composition profiles have been obtained using Glow Discharge Optical Emission Spectrometry and localized Energy Dispersive X-Ray Diffraction. The micro-hardness and adhesion properties of the different treatments have been evaluated using Vickers micro-hardness tests at different load conditions and confronting the hardness vs load profiles. The tribological behavior of the different treatments has been tested in dry conditions in alternate pin-on-flat configuration. The standalone PVD coatings showed a limited tribological resistance due to the low hardness of the substrate, which resulted in fractures and delamination. The combination of a hardening process followed by a deposition of a PVD coating showed to strongly improve the tribological resistance of Ti-6Al-4 V. Graphical abstract: Highlights: Thin ceramic coating often fail if applied on titanium due to lack of support. Combined PVD/diffusive treatments showed an increase in wear resistance. N ions at 900 °C penetrated deeper inside titanium when compared to C at 800 °C. Nitrided samples caused wear of the counter-material and deposition of titanium on the sample surface. Carburized samples were wear resistance and did not cause damaging of the counter material.